Association between eGDR and MASLD and liver fibrosis: a cross-sectional study based on NHANES 2017–2023 - Peng, Wenjing; Li, Zeyu; Fu, Nian (Frontiers in Medicine, 2025)
BackgroundThis study aimed to investigate the association between estimated glucose disposal rate (eGDR) and metabolic dysfunction-associated steatotic liver disease (MASLD), as well as liver fibrosis, using data from the National Health and Nutrition Examination Survey (NHANES) 2017–2023 dataset.MethodsData from 7,855 participants in the NHANES 2017–2023 dataset were analyzed. Multivariable logistic regression models were constructed to assess the association between eGDR (both continuous and quartiles) and MASLD, as well as liver fibrosis, adjusting for potential confounders. Generalized additive models (GAM) were used to explore non-linear relationships, stratified by age, hypertension, diabetes, cardiovascular disease (CVD), and body mass index (BMI). A two-piecewise linear regression model was used to examine threshold effects. Subgroup analyses were conducted to assess effect modification. Mediation analysis was performed to determine the role of the atherogenic index of plasma (AIP). Sensitivity analysis was performed to test the robustness of the results.ResultsIn the fully adjusted model, higher eGDR was inversely associated with both MASLD and liver fibrosis (MASLD: OR = 0.62, 95% CI: 0.53–0.72, p < 0.0001; liver fibrosis: OR = 0.50, 95% CI: 0.42–0.58, p < 0.0001). Participants in higher eGDR quartiles (Q2, Q3, and Q4) had progressively lower odds of both MASLD and liver fibrosis compared to those in Q1 (MASLD: Q2: OR = 0.56, 95% CI: 0.37–0.84, p = 0.0047; Q3: OR = 0.25, 95% CI: 0.12–0.50, p = 0.0001; Q4: OR = 0.13, 95% CI: 0.05–0.31, p < 0.0001; liver fibrosis: Q2: OR = 0.24, 95% CI: 0.13–0.44, p < 0.0001; Q3: OR = 0.06, 95% CI: 0.02–0.16, p < 0.0001; Q4: OR = 0.05, 95% CI: 0.01–0.19, p < 0.0001). A non-linear relationship with threshold effects at an eGDR value of 3.25 was observed for MASLD. Subgroup analyses revealed that the inverse association between eGDR and MASLD was more pronounced in individuals without diabetes. Additionally, smoothing curve fitting showed that the dose–response relationship between eGDR and both MASLD and liver fibrosis differed by metabolic and clinical status. Mediation analysis suggested that AIP partially mediated the association between eGDR and MASLD, accounting for approximately 10.6% of the total effect. Sensitivity analyses excluding extreme eGDR values confirmed the robust inverse associations with MASLD and liver fibrosis.ConclusionThis study found a significant non-linear inverse association between eGDR and both MASLD and liver fibrosis, with a threshold effect observed for MASLD. The association was stronger in non-diabetic individuals and partially mediated by AIP. Moreover, the dose–response relationships varied across metabolic and clinical subgroups.